Combined Strength and Endurance Training Improves Health-Related Quality of Life in Healthy Middle-Aged and Older Adults - Sillanpää, E.; Häkkinen, K.; Holviala, J.; Häkkinen, A. (International Journal of Sports Medicine, 2012)
The purpose of this study was to evaluate the effects of 21 weeks of strength and/or endurance training on health related quality of life (HRQoL) in 39–77 year-old healthy subjects. 108 men and 96 women were randomized into endurance, strength, or combined training groups and controls. Strength-group performed high-intensity strength training while endurance-group performed cycle training. Combined-group completed both training protocols. Leg extension strength and maximal oxygen uptake were measured. HRQoL was assessed with a Finnish version of SF-36 questionnaire. A significant training-induced difference was observed between groups (p=0.038) in the vitality dimension of HRQoL, which was characterized by a 6.6±1.5 unit increase in the combined group and no change in the other groups. Both endurance and combined training showed small improvements in certain dimensions of HRQoL. Dimensions of general (4.6±1.9) and mental health (3.9±1.4) improved in combined-group while general health (4.4±2.0), bodily pain (5.5±2.5) and role physical (6.0±2.4) improved in endurance-group. Strength-group experienced increased pain ( − 5.4±1.8) during the experimental period. However, increased perception of pain was not observed during combined training. According to the present results both endurance and especially combined training may have potential to promote or maintain certain dimensions of HRQoL even in middle-aged and older adults.
Keywords: health related quality of life; RAND-36; strength training; endurance training